2019
DOI: 10.1175/jcli-d-19-0051.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Global Warming Impacts on Madden–Julian Oscillation Precipitation Amplitude

Abstract: Mechanisms that cause changes in Madden–Julian oscillation (MJO) precipitation amplitude under global warming are examined in models from phase 5 of the Coupled Model Intercomparison Project. Under global warming in representative concentration pathway 8.5, MJO precipitation intensifies in most models relative to current climate while MJO wind circulations increase at a slower rate or weaken. Changes in MJO precipitation intensity are partially controlled by changes in moisture profiles and static stability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 64 publications
(76 reference statements)
4
31
0
Order By: Relevance
“…Given these impacts of the MJO in current climate, an increasing interest exists in understanding how the MJO might change under global warming (Maloney et al, ). Global climate models (GCMs) generally find that MJO precipitation amplitude change ranges from −10% to +20% while MJO circulation strength increases at a slower rate or even weakens (by 1–10%) in the presence of substantial global mean temperature warming (Adames et al, , ; Arnold et al, , ; Bui & Maloney, , ; Chang et al, ; Rushley et al, ; Takahashi et al, ). Bui and Maloney () documented end of the 21st century (2081–2100) MJO precipitation and wind anomaly amplitude changes in several Coupled Model Intercomparison Project phase 5 (CMIP5) models forced with Representative Concentration Pathway 8.5 (RCP8.5) and explained the systematic weakening of MJO wind amplitude or lower rate of increase relative to precipitation amplitude through increases in tropical dry static stability using weak temperature gradient (WTG) theory (e.g., Sobel & Bretherton, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these impacts of the MJO in current climate, an increasing interest exists in understanding how the MJO might change under global warming (Maloney et al, ). Global climate models (GCMs) generally find that MJO precipitation amplitude change ranges from −10% to +20% while MJO circulation strength increases at a slower rate or even weakens (by 1–10%) in the presence of substantial global mean temperature warming (Adames et al, , ; Arnold et al, , ; Bui & Maloney, , ; Chang et al, ; Rushley et al, ; Takahashi et al, ). Bui and Maloney () documented end of the 21st century (2081–2100) MJO precipitation and wind anomaly amplitude changes in several Coupled Model Intercomparison Project phase 5 (CMIP5) models forced with Representative Concentration Pathway 8.5 (RCP8.5) and explained the systematic weakening of MJO wind amplitude or lower rate of increase relative to precipitation amplitude through increases in tropical dry static stability using weak temperature gradient (WTG) theory (e.g., Sobel & Bretherton, ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, WTG theory indicates weakening large‐scale vertical motion per unit apparent heating given increases in tropical dry static stability in a warming climate (e.g., Wolding et al, ). A follow‐up study suggested that changes in MJO precipitation amplitude at the end of the 21st century are regulated by competing effects from an increased lower tropospheric moisture gradient and more top‐heavy MJO diabatic heating profile with warming (Bui & Maloney, ). How the MJO changes in earlier decades of the 21st century (2021–2080) remains less thoroughly investigated, in particular how soon MJO changes in response to anthropogenic greenhouse gas (GHG) increases can be detected relative to the historical period given the nonlinear and chaotic nature of the climate system (e.g., Cassou et al, ; Kirtman, ).…”
Section: Introductionmentioning
confidence: 99%
“…The area with the highest SST was concentrated in the central area of the Pacific Ocean and the Indian Ocean. In the eastern part of Africa and the southern part of Asia and the Indian Ocean, the average SST has increased from [22,27] to [27,30]. The increase in SST near the west coast of Canada was consistent with the rise in the average temperature in the coastal area, thereby the contribution of SST to climate change cannot be neglected.…”
Section: End Trainingmentioning
confidence: 94%
“…Using the existing literature and official government documents as a reference, some original indicators affecting climate change can be selected [26,27]. However, the quality of the information varies greatly, therefore information from the academic literature is dominant, which is supplemented by information obtained from other channels.…”
Section: The Climate Change Modelmentioning
confidence: 99%
See 1 more Smart Citation